From Tradition to Transformation: Exploring Institutional Leadership Models Rooted in Local Cultural Wisdom - Ibrahim, Muchlis; Burhanudin, Burhanudin; Suprayati, Nely; Fahmi, M. Nurul; Sahaluddin, Sahaluddin (JURNAL AL-TANZIM, 2025)
This study aims to explore the application of a leadership model based on local cultural wisdom. The focus of this study is to examine how local values, such as cooperation, deliberation, and social responsibility, influence the leadership process and decision-making. This study uses a qualitative approach with a case study design. Data collection was conducted through interviews, observations, and documentation studies, which were then analyzed through the stages of data reduction, data presentation, and conclusion. The findings demonstrate that a leadership model grounded in local values is capable of fostering social cohesion, collective responsibility, and inclusive decision-making. Programs such as community-based skills training and the construction of public facilities demonstrate the importance of cooperation and shared responsibility. The use of deliberation in the decision-making process ensures the involvement of all stakeholders, resulting in more effective and culturally relevant decisions. Additionally, the institution's commitment to preserving local culture while responding to modern challenges enhances its long-term sustainability. This study demonstrates that integrating local wisdom into leadership practices can improve institutional effectiveness and community engagement. Future research is recommended to explore the application of this model in other community-based organisations.